The role of neutrophil-lymphocyte ratio, platelet-lymphocyte ratio, crp and albumin to predict postoperative one-year mortality in patients with hip fractures - Niyazi Igde; Mustafa Yerli; Ali Yuce; Mustafa Bugra Ayaz; Hakan Gurbuz (Medicine Science, 2022)
Elderly patients are espcialy at high risk for postoperative complications. This is even more important following hip fracture surgery due to its fragility and comorbidities. Using certain biomarkers may be an interesting way of tackling the question of optimal patient management. In this study we aimed to determine the status of values such as NLR, PLR, albumin, and CRP, which can be easily accessed from blood tests that we routinely use, in predicting mortality in patients who underwent partial prosthesis after hip fractures. Patients over 70 years of age with intertrochanteric femur and collum femoris fractures and who underwent partial endoprosthesis were included in the study. The neutrophil lymphocyte and platelet lymphocyte ratios, albumin values, and CRP values were recorded by examining the hemogram and biochemistry tests taken routinely at the time of admission to the hospital, 1 day before the surgery and on the 1st post-operative day. The distribution of clinical and socio-demographic characteristics of individuals according to their survival within the scope of the study has elaborated that there is a statistically significant difference in terms of age, gender, diagnosis, time to surgery (days) of the deceased and surviving individuals. It is observed that the majority of the patients who died were women and were diagnosed with collum femoris. It was determined that there was a statistically significant difference only in CRP and albumin values between the two groups in postoperative parameters. According to the outcomes of this analysis one can conclude that NLR and PLR values measured preoperatively on the hemogram panel can be used to predict 1-year mortality. Regardless of the fracture period, low albumin value is seen as an independent variable in predicting mortality. [Med-Science 2022; 11(2.000): 729-33]